Research on computer system collecting the vault techniques - Liu, L.; Zhou, J. H.; Gao, Z. L. (Applied Mechanics and Materials, 2013)
We protocol to research and develop sport biomechanics quick response system for vault technical training, which quick analyzes vault techniques of athletes by using pressure plate on vault board to collect data of step position and strength, combined with synchronous acquisition of coxa joint kinematic parameters. This is helpful to improve the technical training effective of vault gymnast.